Reducing post-radical cystectomy complications with enhanced recovery after surgery (ERAS) protocol: is it time to change? - Ahmad Zulfan Hendri; Muhammad Mauny Puteh; Said Alfin Khalilullah; Andy Zulfiqqar (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Radical cystectomy (RC) remains associated with a greater number of postsurgical complications than any urological procedure. Enhanced recovery after surgery (ERAS) protocol is a multimodal perioperative care pathway designed to achieve early postsurgical recovery. We evaluated the perioperative outcome of post-RC patients, comparing the effectiveness of ERAS to conventional recovery protocols. We identified 37 patients who underwent RC for bladder cancer from 2016 to 2018. The characteristics, complication rate and clinical outcomes were evaluated in these groups of patients. In this study, the mortality was 8.1%, and the complications were 37.8%. The most frequent complications were anastomotic leakage (16.2%), wound dehiscence (13.5%), infections/sepsis (8.1%), and paralytic ileus (8.1%). The ERAS protocol significantly reduced operative time (p=0.001; OR=216; CI95%: 12.0-3855.2) and reduced overall complications (p=0.04; OR= 0.14 CI95%: 0.016-1.132). Extensive complications and mortality develop following the RC procedure. Meanwhile, refinement in perioperative care has been reducing the rate of serious complications. The ERAS protocol distinctly reduces the post-RC complication rate.